Simple Preparation of a Waterborne Polyurethane Crosslinked Hydrogel Adhesive With Satisfactory Mechanical Properties and Adhesion Properties - Shen, Jiahao; Zhang, Heng; Zhu, Jingxin; Ma, Yanlong; He, Hongwei; Zhu, Fengbo; Jia, Lan; Zheng, Qiang (Frontiers in Chemistry, 2022)
Waterborne polyurethane has been proven to be an ideal additive for the preparation of hydrogels with excellent mechanical properties. This work reports that a satisfactory adhesion of acrylamide hydrogels can be obtained by introducing a large amount of waterborne polyurethane into system. A series of polyurethane hydrogels was prepared by using one-pot method with acrylamide monomer and 2-hydroxymethyl methacrylate end-modified waterborne polyurethane emulsion. The hydrogels exhibit good strength (greater than 30 KPa), wide range of adjustable strain (200%–800%), and excellent compression fatigue resistance. The performance improvement is attributed to the fact that the polyurethane emulsion containing double bonds provides chemical crosslinking and forms polyurethane microregions due to hydrophilic and hydrophobic interactions. The hydrogel shows extensive and repeatable adhesion on diverse substrates. This simple preparation method through polyurethane crosslinked hydrogels is expected to become a low-cost and efficient preparation strategy for hydrogel adhesives.